Herpes simplex virus VP16 rescues viral mRNA from destruction by the virion host shutoff function. - Lam, Q (1996)
Herpes simplex virus (HSV) virions contain two regulatory proteins that facilitate the onset of the lytic cycle: VP16 activates transcription of the viral immediate-early genes, and vhs triggers shutoff of host protein synthesis and accelerated turnover of cellular and viral mRNAs. VP16 and vhs form a complex in infected cells, raising the possibility of a regulatory link between them. Here we show that viral protein synthesis and mRNA levels undergo a severe decline at intermediate times after infection with a VP16 null mutant, culminating in virtually complete translational arrest. This phenotype was rescued by a transcriptionally incompetent derivative of VP16 that retains vhs binding activity, and was eliminated by inactivating the vhs gene. These results indicate that VP16 dampens vhs activity, allowing HSV mRNAs to persist in infected cells. Further evidence supporting this hypothesis came from the demonstration that a stably transfected cell line expressing VP16 was resistant to host shutoff induced by superinfecting HSV virions. Thus, in addition to its well known function as a transcriptional activator, VP16 stimulates viral gene expression at a post-transcriptional level, by sparing viral mRNAs from degradation by one of the virus-induced host shutoff mechanisms.